2006
DOI: 10.1007/s10661-005-9115-3
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Conditions and Correlations of Sediment Quality Triad Indicators in Delaware Bay

Abstract: This paper summarizes sampling results from NOAA's National Status and Trends (NS&T) Program for marine environmental quality in Delaware Bay. A stratified-random design was used to determine the spatial extent of sediment contamination and toxicity in Delaware Bay from offshore stations in the coastal zone, the lower estuary, the upper estuary, the fresh/salt mixing zone, and tidal fresh areas. Sediment samples were taken for chemical analyses of major classes of environmental contaminants, a suite of toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Similar findings were noted in Delaware Bay (Hartwell and Hameedi 2006;Hartwell and Claflin 2005) and other systems (SCBW 1959). The different habitat groupings noted in Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar findings were noted in Delaware Bay (Hartwell and Hameedi 2006;Hartwell and Claflin 2005) and other systems (SCBW 1959). The different habitat groupings noted in Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Low score sites are distributed between Clear Lake, a heavily urbanized area, and the approach channel. In Delaware Bay (Hartwell and Hameedi 2006;Hartwell et al 2001), stations with ERMq scores above the regression line are found in the section of the Delaware River including the industrialized areas in Philadelphia PA, Camden NJ, and Wilmington DE, all areas of known chemical contamination (Fig. 8).…”
Section: Triad Area<1000mentioning
confidence: 95%
“…Besides sediment budgets, a study concerning contamination was made by Hartwell and Hameedi (2006) to examine the spatial extent of sediment contamination and toxicity from offshore stations to discover that tidal fresh areas and parts of the mixing zone were heavily contaminated. While this is not directly linked to sedimentation processes, it is an additional stressor on the health of wetland plants and animals that can lead to a loss of species diversity and abundance.…”
Section: Research On Delaware Estuary Marshesmentioning
confidence: 99%
“…Natural and anthropogenic changes can have a major impact on their development and health (Allen, 2000;Boorman, 1999;Kraft, Yi, and Khalequzzaman, 1992;Orson, Simpson, and Good, 1992;Vane et al, 2008;Velde and Church, 1999). The Delaware Bay and its fringe marshes are no exception to these stressors, and much work has been carried out to shed some light on the processes and interactions that govern the functioning of marshes in the Delaware Bay (Church et al, 2006;Fletcher, Knebel, and Kraft, 1992;Fletcher et al, 1993;Hartwell and Hameedi, 2006;Kearney et al, 2002;Kraft, Yi, and Khalequzzaman, 1992;Najjar et al, 2000;Orson, Simpson, and Good, 1992;Teal and Peterson, 2005) and worldwide (Cappucci et al, 2004;D'Alpaos et al, 2006D'Alpaos et al, , 2007Marani et al, 2003;Thompson et al, 2004). In addition to this fundamental research, the question has arisen of whether sea level rise and changing sediment budgets have a negative impact on the surrounding fringe of marshes in the Delaware Bay (Church et al, 2006;Kraft, Yi, and Khalequzzaman, 1992;Sommerfield and Madsen, 2003;Velde and Church, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…So, the coastal marine sediments can generally be considered as accumulation areas of contaminants, which can pose a real threat to the marine life and to the health of people (e.g. Carafa et al ., 2006;Hartwell and Hameedi, 2006;Boszke and Astel, 2007;Zonta et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%